Kontradiksi colonizer dengan colonized dalam cerpen Di Mana Kepala JP Coen? - Fadilah, Nurmilah; Ismail, Indira (Universitas Mulawarman, 2024)
Edward Said's concept of orientalism in the short story Di mana Kepala JP Coen? (2024) by Dewanto Amin Sadono raises the complexity of the binary opposition of Indonesia and the Netherlands through stereotypical discursive that causes objectivity towards Indonesia women as mistresses and exotic. This study aims to dismantle the contradiction of views between the Netherlands (colonizer) and the Indonesia (colonized) after the colonial period ended. The method used in the research is in the form of a qualitative descriptive method to clarify the data that describe the construction of orientalism. The data collection technique in this study uses reading, observing, recording, and classifying techniques. The results of this study show the development of binary opposition that describes the Indonesia nation as having oriental traits, such as backward, uncivilized, and exotic, while the West is an ideal nation. The complexity of the binary opposition shows the resistance of indigenous women and the power of the Indonesia nation to dominate the postcolonial historical discourse. Short Story Di mana Kepala JP Coen? (2024) is a criticism of orientalism in the continuation of the meaning of representation of East with West as inferior and superior parties. This is a form towards equality and liberation of the colonized from the colonizer.